PENGARUH RESIDU BAHAN ORGANIK PADA TANAMAN JAGUNG (Zea mays L.) SEBAGAI TANAMAN SELA PERTANAMAN UBI KAYU (Manihot esculenta L.) - T. Islami (BUANA SAINS, 2012)
Maize (Zea mays L) is one of importance as intercrop with cassava (Manihot esculanta L). Field experiment was conducted on Alfisol of Agric Faculty of Brawijaya University Exp Station. The aim of this research was to evaluate the residual effect of organic matter on maize. Randomized Block design was used with seven treatment (control + application of six kinds of organic matter: (1) manure, (2) residu of manure, (3) residu of biochar manure, (4) biochar manure, (5) biochar stem of cassava and (6) residu of biochar stem cassava. Dosage of manure is 15 t/ha. Observation was made for growth and yield of maize. The result showed that there is no significant effect on growth and yield of maize, although applications of manure were higher compared with control. Biochar was potential organic matters as soil amandement